Telephone triage service use is associated with better outcomes among patients with cerebrovascular diseases: a propensity score analysis using population-based data - Ryo Deguchi; Yusuke Katayama; Hoshi Himura; Tetsuro Nishimura; Yuko Nakagawa; Tetsuhisa Kitamura; Shunsuke Tai; Junya Tsujino; Takeshi Shimazu; Yasumitsu Mizobata (Frontiers Media S.A., 2023)
IntroductionThe telephone triage service is an emergency medical system through which citizens consult telephone triage nurses regarding illness, and the nurses determine the urgency and need for an ambulance. Despite being introduced in several countries, its impact on emergency patients has not been reported. We aimed to determine the effect of the telephone triage service on the outcomes of hospitalized patients diagnosed with cerebrovascular disease upon arrival after being transported by an ambulance.MethodsThis retrospective study included patients with cerebrovascular disease who were transported by ambulance between January 2016 and December 2019. The primary outcome was discharge to home by day 21 of hospitalization. A total of 344 patients who used the telephone triage service were propensity score-matched to 344 patients who directly called for an ambulance.ResultsTelephone triage service use was associated with discharge to home by hospital day 21 (crude odd ratio: 1.8; 95% confidence interval: 1.3-2.4) and was not significantly associated with survival on hospital day 21 in multivariate regression analysis.ConclusionThe prognoses of cerebral infarction, intracerebral hemorrhage, and subarachnoid hemorrhage depend on the time from symptom onset to treatment. Telephone triage services may allow patients to receive treatment more rapidly than traditional ambulance requests, resulting in improved patient outcomes. The findings of this study suggest that the use of telephone triage services is associated with improved outcomes in patients with cerebrovascular disease and indicate that the costs for medical expenses and disability may be greatly reduced in an aging society.